Determination of Gamma Oryzanol from Ethanolic Extract of Indonesian Rice Bran (Oryza sativa) - Vardhani, Afifah; Perdanastuti, Hidayah Sunar (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Rice bran contains gamma oryzanol, a chemical compound mostly consisted of complex ester trans-ferulate with phytosterols1. Gamma oryzanol has a strong antioxidant activity, explained by the free radical scavenging activity. This study was aimed to determine gamma oryzanol from ethanolic extract of rice bran. Quantitative analysis was conducted using HPLC analysis with mixture of methanol:acetonitrile:isopropanol (50%:40%:10%) as mobile phase and Inertsil ODS-3 5 μm as stationary phase. The UV detector wavelength was set to 327 nm, and the flow rate was set to 1 mL/min2. Gamma oryzanol standard and rice bran ethanolic extract 96% was injected into HPLC system. Ethanolic extract of rice bran (Oryza sativa) sample showed four major peaks as those of gamma oryzanol standard and contained 105,981 ppm of gamma oryzanol. As the conclusion, ethanolic extract of rice bran (Oryza sativa) contains gamma oryzanol